LAYANAN INFORMASI DIGITAL SEBAGAI STUDI PENELUSURAN ALUMNI S1 PROGRAM STUDI PPKn UNIVERSITAS TERBUKA - Ary Purwantiningsih; Sardjiyo Sardjiyo; Ajat Sudrajat; Septian Aji Permana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to analyze the benefits of digital information services as a search for S1 alumni of the Universitas Terbuka PPKn Study Program.The research method used is the Mixed Method (quantitative and qualitative). The survey method was carried out on graduates from the PPKn S1 study program who graduated from 1998-2013 through a questionnaire sent using a google form. While the qualitative method is carried out through interviews conducted by interviewers who have attended qualitative research training at UT. The instrument was developed by the UT Study Tracer Team by involving expert reviewers. Data was collected in two ways, namely filling out a questionnaire and interviewing. The questionnaires were filled out for the selected sample graduates, graduate supervisors, and graduate colleagues.The results showed that the existence of digital information services as a search for S1 alumni of the Open University Civics Study Program received a good response from users. The alumni find it easy to fill in and get the data needed by alumni. Graduates of the UT PPKn Undergraduate Program received a fairly good appreciation in competitiveness with other university graduates, while for further studies they felt satisfied with the PPKn S1 graduates. they are satisfied because the substance of the field of knowledge obtained in the Civics Undergraduate Study Program because it is in accordance with the needs of the work, there are only a few courses that are not very relevant to the teaching material in junior high school.